Fabrication, characterisation and properties of polysiloxane rice husk silica composites - Azmi, Mohd Azham (2018)
The polysiloxane silica composites were fabricated and characterised as to elucidate the feasibility of casting (CA) and compression (CO) method. Besides, the contribution of rice husk silica (RHA SiO2) and crystalline silica (CS) in enhancing the composites properties were also investigated. Moreover, fabricated composites were applied in hand grinder as a vibration damper and the performance had been analysed. The important issues covered in this study were the contribution of RHA SiO2 instead of using CS as a filler and the investigation of most ideal parameter in improving thermal, physical, mechanical and vibration properties of composites. The polysiloxane composites were analysed and compared with various parameters i.e; composition of fillers (2wt% to 12wt%) and curing temperatures (room temperature (RT), 65 and 100˚C). Addition of 10wt% RHA SiO2 had found to contribute better performance compared to CS addition, accredited to RHA SiO2 density and surface morphology. As for the fabrication effects, CO method was found to offer composites with better tensile and vibration properties. However, as for the thermal behavior, CA method yielded composites with better thermal stability due to better filler distribution on surface of the composites. On the other hand, the increment of curing temperature does not show significant effect in improving thermal properties as the thermal stability were decreased due to interferences of curing network stability. However, the polysiloxane composites cured at 65˚C and 100˚C were found to offer better tensile and vibration properties. Throughout the observations, the maximum perfomance of thermal, tensile and vibration behavior for polysiloxane composites were achieved by addition of 10wt% RHA SiO2, fabricated using CO method and cured at 100˚C.